(untitled) (Journal of Universal Science Research, 2023)
The article examines modern programming language courses in higher education, including their content, teaching technologies used, and Python’s role as an example of a modern programming language. The article compares traditional programming language courses with modern programming language courses, showing the differences in content and teaching methods. The table shows a summary of the comparison between the two types of programming language courses.